1995
DOI: 10.1017/s001667230003295x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and RFLP linkage mapping of a DNA repeat family ofSolanum spegazziniiby which chromosome ends can be localized on the genetic map of potato

Abstract: SummaryIn a random sample of 2263 cloned genomic DNA fragments of the wild potato species Solanum spegazzinii six related, highly repetitive fragments (SPG repeat family) were identified that were present in much higher copy numbers in S. spegazzinii when compared with the closely related cultivated potato S. tuberosum. The SPG repeat family was organized in long arrays of multiple copies. Cross hybridization experiments with 29 wild and cultivated Solanum species and with the related tomato showed specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…More strikingly, the repetitive sequence content and composition of potato and tomato have diverged with impacts seen on genome architecture at both the macro- and the micro-level as evidenced through differences in telomeric-repetitive sequences and rDNA content and in interruption of synteny through transposition of retrotransposons. Our data are consistent with previous reports on repetitive sequences [ 36 - 42 ] which show divergence of this fraction of the genome within the Solanaceae. These data clearly suggest that while these two solanaceous genomes can be cross-leveraged for analysis of gene content and order, they are not interchangeable with respect to all genomic features.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More strikingly, the repetitive sequence content and composition of potato and tomato have diverged with impacts seen on genome architecture at both the macro- and the micro-level as evidenced through differences in telomeric-repetitive sequences and rDNA content and in interruption of synteny through transposition of retrotransposons. Our data are consistent with previous reports on repetitive sequences [ 36 - 42 ] which show divergence of this fraction of the genome within the Solanaceae. These data clearly suggest that while these two solanaceous genomes can be cross-leveraged for analysis of gene content and order, they are not interchangeable with respect to all genomic features.…”
Section: Discussionsupporting
confidence: 93%
“…While the cultivated species have been bred for these diverse agronomic traits, genome sequence analysis has indicated that these species share to a large extent not only genes [ 30 ] but also gene order (synteny) between their genomes [ 31 - 35 ]. While major classes of repetitive sequences are conserved among some Solanaceae species [ 36 , 37 ], lineage-specific repetitive sequences have been reported, suggesting divergence of this fraction of the genome has occurred through evolution [ 36 - 42 ]. With the availability of large genomic datasets for two Solanaceae species, tomato and potato, the extent of sequence conservation as well as synteny can be addressed in a more robust manner.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA sequences that make up subtelomeres are able to substitute, at least to some extent, for the protective role of telomeric DNA sequences in case of telomere loss (Palladino and Gasser 1994). In subtelomeric regions in plants, both tandem and dispersed repeated sequences are found in large excess over single-copy or low-copynumber sequences, and are frequently used as markers for identifying genomic components of hybrid organisms in plant breeding and in taxonomic studies (Gebhardt et al 1995;Vershinin et al 1996). In subtelomeric regions in plants, both tandem and dispersed repeated sequences are found in large excess over single-copy or low-copynumber sequences, and are frequently used as markers for identifying genomic components of hybrid organisms in plant breeding and in taxonomic studies (Gebhardt et al 1995;Vershinin et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few of the >400 RFLP loci mapped on this population are shown. The markers designated PSTR are sub-telomeric repeats indicating the ends of linkage groups(Gebhardt et al 1995). The maps on the right show the position of the SSRs on the Germicopa population.…”
mentioning
confidence: 99%